Just Grace gets crafty - Harper, Charise Mericle (Houghton Mifflin Harcourt, 2014)
"There's a new crossing guard in town named Marie who needs a bit of help making friends, a fun substitute teacher for Miss Lois, and most exciting, Grace and Mimi are going to have their own table at the craft fair"--